DETERMINANTS OF CAPITAL STRUCTURE IN INDONESIAN COMPANIES FROM 2011 - 2022 - Wilar, Gideon Caprio; Budhidharma, Valentino (Milestone: Journal of Strategic Management, 2024)
The purpose of this study is to examine the variables influencing capital structure in Indonesian businesses. The dependent factors in this case are the debt to asset ratio (DAR) and the debt-to-equity ratio (DER), while the independent variables are profitability, growth potential, size, dividend policy, liquidity, and business risk. All industries in Indonesia are represented in the research sample, except for the banking industry. The panel regression analytical method is used. Furthermore, Random Forest's variable importance analysis is used in this work. The outcome demonstrated that dividends, tangibility, profitability, and liquidity are important components of both DAR and DER models. Strong tangible assets raise both DAR and DER, but favorable profitability and liquidity typically lower them. Additionally, businesses that pay out larger dividends typically have smaller debt loads. Therefore, businesses should concentrate on sustaining strong profitability as it is closely related to sales. To guarantee continuous liquidity, which enables businesses to fulfill both short- and long-term obligations, care must be taken while paying out dividends.